Culture and economic transformation: perspectives from India and China/ edited by Surjeet Singh (New Delhi, 2013)
China and India - the two emerging economies with growing influence the world over - are undergoing profound social and cultural changes. China introduced a variety of economic and political reforms in 1978, and India initiated reforms in 1991. These shifts produced significantly higher rates of growth than witnessed during the preceding decades. The rapid pace of economic growth in both countries has transformed their economies in many ways, however economic transformation does not occur in isolation. Culture and social institutions also influence, and are influenced by, the processes of economic change. This book offers a comparative understanding of these two great nations and their diverse social and cultural realities. The book's contributions focus on a wide variety of topics concerning the contemporary societies of each country, such as: the middle classes and consumption patterns * the processes of migrations * labor markets * regional inequalities * housing * gender bias and discrimination * religious life * ethnic minorities.
Keywords: "Economic history, Social change, Jodhka, Surinder 5.4. S"